Self-templated chemically stable hollow spherical covalent organic framework - Kandambeth, Sharath; Venkatesh, V.; Shinde, Digambar B.; Kumari, Sushma; Halder, Arjun; Verma, Sandeep; Banerjee, Rahul (Nature Communications, 2015)
Covalent organic frameworks are a family of crystalline porous materials with promising applications. Although active research on the design and synthesis of covalent organic frameworks has been ongoing for almost a decade, the mechanisms of formation of covalent organic frameworks crystallites remain poorly understood. Here we report the synthesis of a hollow spherical covalent organic framework with mesoporous walls in a single-step template-free method. A detailed time-dependent study of hollow sphere formation reveals that an inside-out Ostwald ripening process is responsible for the hollow sphere formation. The synthesized covalent organic framework hollow spheres are highly porous (surface area similar to 1,500m(2) g(-1)), crystalline and chemically stable, due to the presence of strong intramolecular hydrogen bonding. These mesoporous hollow sphere covalent organic frameworks are used for a trypsin immobilization study, which shows an uptake of 15.5 mu mol g(-1) of trypsin.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.